A rare case of large left atrial myxoma associated with carney syndrome - Kocabeyo?lu, Sinan Sabit; Özyüksel, Arda; Çetin, Erdem (Tehran Heart Center, 2014)
Carney Syndrome (CS) is an autosomal dominant multiple neoplasia syndrome that includes cardiac, endocrine, cutaneous, and neural tumors. Cardiac myxomas can be seen in the course of CS. A 46-year-old female patient was admitted to our clinic with palpitation, cough, and exertional dyspnea. Physical examination revealed pigmented lesions, especially scattered in the neck, chest, and extremities. Echocardiography revealed a left atrial mass, 6 × 4 cm in size, originating from the interatrial septum that was protruding into the left ventricle through the mitral valve during diastole. The tumor was excised from the interatrial septum with its pedicle. The patient was discharged at the fifth postoperative day without any complication. Cardiac myxomas are a cornerstone of this disease since cardiac manifestations and related complications account for the majority of mortality seen in the course of CS.
Keywords: Carney Complex; Multiple Endocrine Neoplasia; Myxoma